Assessing Preoperative Frailty Utilizing Validated Geriatric Mortality Calculators and Their Association With Postoperative Hip Fracture Mortality Risk. (September 2014) - Dwyer, Jennifer G.; Reynoso, Jason F.; Seevers, Georgia A.; Schmid, Kendra K.; Muralidhar, Padmashri; Konigsberg, Beau; Lynch, Thomas G.; Johanning, Jason M.
Introduction: End-of-life surgical care is a major concern with a significant number of operations performed within the last year of life; surgery for hip fractures is a prime example. Unfortunately, no simple objective tool exists to assess life expectancy in the postoperative period. The goal of our study was to analyze 2 simple geriatric life expectancy calculators to compare with the current Veterans Affairs Surgical Quality Improvement Program (VASQIP) postoperative 30-day mortality calculator. Methods: This retrospective study assessed the utility of 3 validated calculators in 47 hip fracture repairs from July 2009 to May 2011. The tools included: 30-day VASQIP mortality calculator, 6-month Minimum Data Set Mortality Risk Index-Revised (MMRI-R), and Four-Year Mortality Index. The VASQIP calculator requires chart review, Current Procedural Terminology (CPT) codes, and laboratory analysis, whereas the mortality risk indices require simple patient questioning if prospective or simple chart review if retrospective. Scoring was performed and mortality risk was compared between survivors and nonsurvivors. Results: A total of 47 hip fractures were repaired during the study period with 37 survivors and 10 nonsurvivors. In all, 7 died within 30 days, 2 died within 6 months, and 1 died greater than 6 months after surgery. The mean age (standard deviation [SD]) of all patients undergoing hip fracture repair was 73.6 (13.3) years. The VASQIP calculator mean (SD) 30-day mortality risk was 10.4% (5.4) for nonsurvivors compared to survivors 4.3% (5.5), P < .003; the MMRI-R mean (SD) mortality risk was 35.8% (15.4) for nonsurvivors compared to survivors 14.7% (9.5), P < .001; the Four-Year Mortality Index mean (SD) mortality risk was 60.9% (16.9) for nonsurvivors compared to survivors 48.9% (24.4), P < .09. Conclusion: Overall, the VASQIP 30-day and MMRI-R 6-month mortality calculators showed significant differences in mortality risk between survivors versus nonsurvivors in a population with hip fracture. In contrast, the Four-Year Mortality calculator may not sufficiently discriminate operative risk. The easily obtained MMRI-R has the potential to provide information on short-term postoperative mortality risk.